2021
DOI: 10.1186/s13104-021-05881-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of bacteriophage BI-EHEC infecting strains of Enterohemorrhagic Escherichia coli

Abstract: Objective The aims of this research were to determine the genomic properties of BI-EHEC to control Enterohemorrhagic Escherichia coli (EHEC), which was isolated from previous study. Genomic analysis of this phage is essential for the assessment of this bacteriophage for further application as food preservatives. Results Genome of BI-EHEC was successfully annotated using multiPhATE2. Structural and lytic cycle-related proteins such as head, tail, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For the bacteriophage to be applied as biocontrol, it is necessary to determine their genomic properties. One of the phage that we used which is BI EHEC have been characterized through genetic analysis, and it was found that there were no virulence properties, antibiotic resistance genes as well as lysogenic protein among annotated genes which implied BI-EHEC a lytic life cycle [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the bacteriophage to be applied as biocontrol, it is necessary to determine their genomic properties. One of the phage that we used which is BI EHEC have been characterized through genetic analysis, and it was found that there were no virulence properties, antibiotic resistance genes as well as lysogenic protein among annotated genes which implied BI-EHEC a lytic life cycle [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, scientists reported the isolation of diverse phages in SEA from different sample types, with potential activities against human pathogens (Table 2). Among the phages discovered in the region with notable activity against MDR organisms are: (1) phages vB_AbaM_PhT2 (Styles et al, 2020) and AB1801 (Wintachai et al, 2019), which exhibited anti-MDR A. baumannii activity, in vitro and in vivo, respectively, (2) phage UPM2146 (Assafiri et al, 2021), which exhibited activity against carbapenem-resistant K. pneumoniae, in vitro and in vivo, (3) phage C34 (Guang- Han et al, 2016), which controlled naturally resistant Burkholderia pseudomallei bacterial load, in vivo, (4) phage ΦHN10 (Phothichaisri et al, 2018), which exhibited the highest breadth of activity against various Clostridiodes difficile strains, in vitro, (5) phage ΦKAZ14 (Ahmad et al, 2015), which induced lysis of extended-spectrum betalactamase (ESBL)-producing Escherichia coli, in vitro, (6) phages UPMK_1 and 2 (Dakheel et al, 2019) and ΦNUSA-1 and 10 (Tan et al, 2020), which all exhibited lytic activity against methicillin-resistant Staphylococcus aureus (MRSA), and antibiofilm activity for the first two phages in in vitro experiments, (7) cocktail of phages vB_SenS_WP109, WP110, and WP128 (Pelyuntha et al, 2021), which induced lysis of multiple MDR Salmonella serovars, in vitro, and (8) phages KP1, 2 Poultry and farm feces, urban catchment, tissue samples Indonesia, Malaysia, Singapore Lau et al, 2012;Gan et al, 2013;Rezaeinejad et al, 2014;Ahmad et al, 2015;Vergara et al, 2015;Sellvam et al, 2018;Lukman et al, 2020;Dewanggana et al, 2021;Sjahriani et al, 2021;Waturangi et al…”
Section: Phages In Seamentioning
confidence: 99%
“…WGS can be used as a crude screening method for choosing the ideal therapeutic strain. In SEA, novel phages have been screened using WGS for their lysogenic and endotoxin production potentials (Gan et al, 2013;Lal et al, 2016a;Wirjon et al, 2016;Thanh et al, 2020;Dewanggana et al, 2021;Nuidate et al, 2021), which are important properties to avoid in choosing therapeutic phages. WGS can also aid in the more detailed classification and identification of the phages, as also applied in SEA strains with promising therapeutic potentials (Gan et al, 2013;Hoai et al, 2016;Lal et al, 2016a,b;Wirjon et al, 2016;Sellvam et al, 2018;Handoko et al, 2019;Thanh et al, 2020;Tu et al, 2020;Nuidate et al, 2021).…”
Section: Phase One: Extensive Phage Isolation and Characterizationmentioning
confidence: 99%